Pengaruh Penggunaan Cassiavera (Cinnamommum burmannii) Mutu Rendah Terhadap Kualitas Oleoresin - Silfia Silfia (Institution for Industrial Research and Standardization of Industry - Padang, 2013)
Low grade cinnamon (Cinnamommum burmannii) such as grade B, C , KA, KB and KC is cinnamon produced from bark of twigs and branches, the most part of them is not scraped with clean, range of color between brownish dark yellow to blackish brown, less spicy flavor, and consists of chips. The purpose of this research to increase the added value of low grade Cassiavera became oleoresin in order to be more efficient of its utilize in industry and avoid from contamination of microorganisms so that can be improved the economic value. The research was conducted with variations of source of Cassiavera raw materials that consisted of treatment A (Cassiavera grade A as a control), B (Cassiavera grade C), C (Cassiavera grade A broken, D (Cassiavera grade KB), and E (Cassiavera grade KC). To produce oleoresin, Cassiavera powder 40 mesh sieve was extracted for 2x2.5 hours at 50°C in 95% ethanol in ratio 1:6. Results of the research were obtained that the best treatment come from Cassiavera grade A broken with the highest yield of oleoresin and cinnamaldehyde obtained were 32.85% and 62.84%, low specific gravity 1.008 and refractive index 1.507, moreover results of the moisture content and ash content analysis of raw material were 10.97% and 2.982% respectively.ABSTRAKCassiavera (Cinnamommum burmannii) mutu rendah (grade B, C, KA , KB dan KC) merupakan cassiavera yang berasal dari kulit ranting dan dahan, sebagian besar tidak terkikis dengan bersih, berwarna kuning tua kecoklatan sampai coklat kehitaman, rasa kurang pedas, dan terdiri dari kepingan. Tujuan penelitian adalah untuk meningkatkan nilai tambah cassiavera mutu rendah menjadi oleoresin agar penggunaannya dalam industri lebih effisien dan terhindar dari pencemaran mikroorganisme sehingga dapat ditingkatkan nilai ekonomisnya. Penelitian dilakukan dengan memvariasikan sumber bahan baku cassiavera yaitu perlakuan A (Casiavera mutu A, sebagai kontrol), B (Cassiavera mutu C), C (Cassiavera mutu A pecahan), D (Cassiavera mutu KB), dan E (Cassiavera mutu KC). Dalam pembuatan oleoresin, cassiavera diekstrak selama 2x2,5 jam pada suhu 50°C dengan pelarut etanol teknis 95% dengan perbandingan 1:6 dari bubuk cassiavera yang lolos ayakan 40 mesh. Dari hasil penelitian diperoleh perlakuan terbaik berasal dari cassiavera A pecahan dengan rendemen oleoresin dan sinamaldehid tertinggi yaitu 32,85% dan 62,84%, berat jenis dan indek bias yang rendah yaitu 1,008 dan 1,507 serta kadar air dan kadar abu bahan baku adalah 10,97% dan 2,982%.